Democratising the Museum Reflections on Participatory Technologies (Edition 1) - Runnel, Pille; Pruulmann-Vengerfeldt, Pille (Peter Lang International Academic Publishing Group, 2014)
Democratising the museum is a collection of articles reflecting upon the problem of how participation, technologically mediated or not, can support the museum in the process of becoming more accessible. The open museum shares power with its visitors while negotiating professionalism and the role of the museum in a modern society. The book looks at the roles and struggles of audiences/visitors and professionals and the role of digital technologies in supporting the participatory museum. While different chapters draw on a variety of empirical examples, the main analytical backbone of the book comes from an extended participatory action research study conducted at the Estonian National Museum. This book aims at both academics and professionals working in the museum field.